Healthcare providers' knowledge and attitudes about overdose prevention sites in Colorado - Emily Paz; Vahid Mashhouri; Mark E. Payton; Brian D. Schwartz; Rachel M.A. Linger (BMC, 2024)
Abstract Background Overdose prevention sites (OPS) are a harm reduction strategy that offer people who use drugs a variety of resources including but not limited to sterile supplies, linkage to healthcare resources, and intervention if an overdose occurs. OPS operate in over 120 countries and evidence has demonstrated they are an effective harm reduction strategy. Despite their success elsewhere, OPS remain federally illegal in the United States and thus there is limited research on their implementation and outcomes in the United States. This study aimed to identify Colorado healthcare providers' knowledge and attitudes about OPS and determine if there is a correlation between healthcare providers with more knowledge about OPS having a more positive attitude about OPS. Methods An electronic survey was distributed to healthcare providers in Colorado. Responses were collected in early 2022 and recorded on a 5-point Likert scale. Mean scores between 1 and 5 were calculated for each participant and analysis of variance methods were used to determine correlating demographic factors. A p value of ≤ 0.05 was used to determine statistical significance of all findings. Results This study included 698 participants. A Pearson correlation analysis revealed a strong positive relationship (r = 0.76, p < 0.0001) between provider knowledge and attitudes about OPS. Emergency medicine providers scored the highest in mean knowledge and attitude scores in comparison to all other specialties. Respondents affiliated with a harm reduction center exhibited the highest mean knowledge and attitude scores. Mean knowledge and attitude scores generally rose with respondents' increasing encounters with people who inject drugs in a typical workday, except when reaching nine or more encounters, where a sharp decline occurred. Conclusions Our study highlights the importance of education, exposure to harm reduction strategies, and inter-specialty collaboration in shaping healthcare providers' knowledge and attitudes about OPS. The positive correlation between providers' knowledge and attitudes about OPS suggests that educating healthcare providers on harm reduction strategies, specifically OPS, may lead to reduced stigmatization of OPS among healthcare professionals.